Controlling Textuality: A Call for a Return to the Senses - Howes, David (Anthropologica, 2022)
This essay traces the involution of anthropological understanding from the 1950s to the present. It is shown that as the conception of "doing ethnography" changed from sensing patterns to reading texts, and from reading texts to writing culture, so too did the content of anthropological knowledge change from being multi-sensory to being self-centred. The essay also proposes a way of escaping the tunnel-vision of contemporary (post-modern) ethnography - namely, by treating cultures as constituted by a particular interplay of the senses which the ethnographer must simulate before making any attempt to describe or evoke the culture under study.